ISLAMIC ECONOMICS AND PAYLATER PRACTICES IN THE DIGITAL SHOPPING ERA: A SYSTEMATIC LITERATURE REVIEW - Rizka Fatkhin Nisa (SHACRAL: Shari'ah Economics Review Journal, 2025)
The rapid expansion of the digital economy has fundamentally transformed consumer behavior, particularly through the emergence of Buy Now, Pay Later (BNPL) or paylater services. These financial innovations offer instant credit access and flexible payment schemes, making them increasingly popular in digital shopping platforms. In Indonesia, the widespread adoption of paylater services has been driven by the growth of e-commerce, fintech innovation, and changing consumption patterns among younger generations. Despite their economic convenience, paylater practices raise critical concerns related to excessive consumerism, household indebtedness, and financial vulnerability. From the perspective of Islamic economics, these concerns are particularly significant due to the prohibition of interest (riba), excessive uncertainty (gharar), and unethical consumption behavior. This article aims to systematically review existing literature on paylater practices within the framework of Islamic economics, focusing on their ethical, legal, and socioeconomic implications in the digital shopping era. Using a qualitative systematic literature review approach, this study synthesizes findings from peer-reviewed national and international journals, academic books, and institutional reports related to Islamic economics, digital finance, consumer behavior, and fintech regulation. The literature is analyzed thematically to identify key issues, scholarly debates, and areas of convergence and divergence between paylater practices and Islamic economic principles. The review reveals that while paylater services contribute to financial inclusion and digital economic growth, their prevailing contractual structures and fee mechanisms often resemble interest-based credit, raising concerns regarding sharia compliance. Moreover, empirical studies highlight the association between paylater usage and increased impulsive consumption, debt accumulation, and financial stress. This article concludes that Islamic economics offers a critical ethical framework for evaluating paylater practices and underscores the need for sharia-compliant digital financing models that balance consumer convenience with financial responsibility and social welfare.